Histamine H2 receptor antagonist exhibited comparable all-cause mortality-decreasing effect as β-blockers in critically ill patients with heart failure: a cohort study - Zhang, Xue-Sha; Cai, Wen-Ke; Wang, Ping; Xu, Ran; Yin, Sun-Jun; Huang, Yan-Hua; Guo, Yu; Jiang, Fang-Fang; Pan, Jian-Mei; Li, Yi-Hua; He, Gong-Hao (Frontiers in Pharmacology, 2023)
Background: Our previous study reported that histamine H2 receptor antagonists (H2RAs) exposure was associated with decreased mortality in critically ill patients with heart failure (HF) through the same pharmacological mechanism as β-blockers. However, population-based clinical study directly comparing the efficacy of H2RAs and β-blockers on mortality of HF patients are still lacking. This study aims to compare the association difference of H2RAs and β-blockers on mortality in critically ill patients with HF using the Medical Information Mart for Intensive Care III database (MIMIC-III). Methods: Study population was divided into 4 groups: β-blockers + H2RAs group, β-blockers group, H2RAs group, and Non-β-blockers + Non-H2RAs group. Kaplan–Meier curves and multivariable Cox regression models were employed to evaluate the differences of all-cause mortalities among the 4 groups. Propensity score matching (PSM) was used to increase comparability of four groups. Results: A total of 5593 patients were included. After PSM, multivariate analyses showed that patients in H2RAs group had close all-cause mortality with patients in β-blockers group. Furthermore, 30-day, 1-year, 5-year and 10-year all-mortality of patients in β-blockers + H2RAs group were significantly lower than those of patients in β-blockers group, respectively (HR: 0.64, 95%CI: 0.50-0.82 for 30-day; HR: 0.80, 95%CI: 0.69-0.93 for 1-year mortality; HR: 0.83, 95%CI: 0.74-0.93 for 5-year mortality; and HR: 0.85, 95%CI: 0.76-0.94 for 10-year mortality, respectively). Conclusion: H2RAs exposure exhibited comparable all-cause mortality-decreasing effect as β-blockers; and, furthermore, H2RAs and β-blockers had additive or synergistic interactions to improve survival in critically ill patients with HF.